Placing researcher identifications: labs, offices and homes in the PhD. Issue 2 (1st December 2016) - Dowling, Robyn; Mantai, Lilia
Abstract : Recent and ongoing changes in university structures and desires, as well as alterations in doctoral education, are shaping new spatialities and temporalities of academic work and identities. This paper considers the spatialities of one set of researcher identities – those undertaking PhD degrees – and specifically explores the material and socio‐cultural affordances of the sites in which research is practised. Based on a qualitative study (interviews with 30 PhD students and focus groups with 34 students) at two Australian metropolitan and research‐intensive universities, we find students associate different forms of researcher identities with the different spaces of research work. In particular, the university campus and specifically the office and/or laboratory are sites where research is approached as a form of work, and identification as both worker and researcher. Notably, social connections and the power relations of the campus are woven through these identifications. Home, in contrast, can serve as a place of respite or a quiet space to think, but more often disrupts identifications as researcher or emergent academic. This research suggests the need first, to recognise the significance of a physical workspace on campus for developing researchers and second, for a more nuanced consideration of the notion of a neoliberalised university.